Benchmarking vs. assessments — A matter of taste, teamwork, and trust. Issue 7 (25th October 2019) - Skipworth, Stan
Abstract : Over the course of this summer, I enjoyed my subscription to the MasterClass online series, in which accomplished professionals in a variety of fields provide insights and highly developed strategies for viewers to incorporate into their own opportunities in the same arena. I was especially intrigued by one episode from James Suckling, a world‐class sommelier, who discussed blind tastings, among other techniques, to build expertise and deeper understanding of the making of wine.